2020
DOI: 10.2147/dddt.s236586
|View full text |Cite
|
Sign up to set email alerts
|

<p>Reversible Small Molecule Inhibitors of MAO A and MAO B with Anilide Motifs</p>

Abstract: Background: Ligands consisting of two aryl moieties connected via a short spacer were shown to be potent inhibitors of monoamine oxidases (MAO) A and B, which are known as suitable targets in treatment of neurological diseases. Based on this general blueprint, we synthesized a series of 66 small aromatic amide derivatives as novel MAO A/B inhibitors. Methods: The compounds were synthesized, purified and structurally confirmed by spectroscopic methods. Fluorimetric enzymological assays were performed to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 59 publications
(64 reference statements)
1
6
0
Order By: Relevance
“…The results were coincided to the studies that the rational design of two phenyl/heteroaryl rings connected via a short linker could lead to potent inhibitors targeting MAO-B and MAO-A. [31,32] Recently, Mathew et al reported that fluorinated morpholine-based chalcones (f1-f3) exhibited potent inhibitory activity and high SI towards recombinant human MAO-B (IC 50 = 0.21 to 0.087 μM; SI = 47.6 to 517.2). [24] The molecular selectivity could be also modulated on the basis of electron donating and withdrawing substitutions on the rings and depended on the length and the degree of conjugation of linker.…”
supporting
confidence: 80%
“…The results were coincided to the studies that the rational design of two phenyl/heteroaryl rings connected via a short linker could lead to potent inhibitors targeting MAO-B and MAO-A. [31,32] Recently, Mathew et al reported that fluorinated morpholine-based chalcones (f1-f3) exhibited potent inhibitory activity and high SI towards recombinant human MAO-B (IC 50 = 0.21 to 0.087 μM; SI = 47.6 to 517.2). [24] The molecular selectivity could be also modulated on the basis of electron donating and withdrawing substitutions on the rings and depended on the length and the degree of conjugation of linker.…”
supporting
confidence: 80%
“…In the exploration of novel, selective, and reversible MAO-B inhibitors, a general blueprint of drug design has been widely accepted recently, and it consists of a molecular framework of two hydrophobic rings of phenyl/heteroaryl, which are separated by an electron-rich and flexible short spacer unit ( Figure 1 ) [ 11 ]. Many of the molecules from this diverse class, such as pyrazolines, enamides, carboxamides, and α, β-unsaturated ketones, were identified as potent MAO-B inhibitors [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…MAO-B, which degrades benzylamine and phenethylamine, is highly expressed in the central nervous system (CNS). Tryptamine, tyramine, and dopamine can be metabolized by both isoforms with individual metabolic activity for each substrate [6][7][8]. In light of all this information, the development of new MAO inhibitors (MAOIs) for the treatment of numerous neurological and psychiatric disorders represents a very important and useful approach [9,10].…”
Section: Introductionmentioning
confidence: 99%